SOSIALISASI GANGGUAN BELAJAR ANAK USIA DINI TERHADAP KESIAPAN MEMASUKI SEKOLAH DASAR: Socialization of Early Children’s Learning Disorders on Readiness to Enter Primary School - Moy, Jesicha; Amseke, Fredericksen Victoranto (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
Socialization of learning disorders in early childhood as a preventive and educational effort to increase the understanding of parents, educators and the community regarding barriers to cognitive development that can affect children's readiness to enter elementary school. The community service method is a qualitative method, lectures, interactive, learning discussions about learning disorders affecting learning readiness to enter elementary school involving 28 parents and 2 teachers at PAUD Diaspora Oesapa Danau Ina. The results of this community service activity found that parents and teachers were able to understand knowledge about the early signs of learning disorders and the importance of early detection and appropriate intervention. This activity can increase awareness among parents and teachers to support children's readiness to enter elementary school optimally, both cognitively, socially-emotionally, and motorically. This activity recommends collaboration between schools, families and professional experts in dealing with children who experience learning disorders